KEANEKARAGAMAN LALAT (Cyclorrapha: Diptera) PADA LOKASI PENJUALAN IKAN KERING DI KOTA PADANG - Syafrina, Syafrina; Jasmi, Jasmi; Zeswita, Armein Lusi (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ Fly is one of insect included into ordo Diptera which has a pair of wing organized as membrane. Fly has cosmopolitan feature where the fly life is gotten smooth almost in the surface of earth. Dealing with it has been conducted research about the diversity of fly (Cyclorrapha: Dipetra) at the area of dry fish disposal in the Padang City. This research was conducted from June to August 2013 conducted at the area of dry fish disposal in the Raya Market Padang, Lubuk Buaya Market Padang and Bandar Buat Market Padang. The research was survey research and description analysis by identification at Animal taxonomi Laboratory of Andalas University Padang . Fly collection was conducted by using 2 methods such as sweap method, and baiting method. The identification result of fly diversity on the third research area was gotten 5 kinds of fly from 3 families and a sub ordo such as Musca domestica, Crysomya megacephala, Calliphora sp., Lucilia sp, and Sarchophaga sp., Musca domestica constituting number of fly which was most dominant got from the third area of sample taking.Â